The Effectiveness of Psychoeducation for Psychological Problems in Adolescents: A Systematic Literature Review - Rahadatul Aissy (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2026)
Adolescence is a critical transitional phase that is vulnerable to various psychological dynamics. One intervention that has emerged to support adolescent mental health is psychoeducation. This study aims to review the effectiveness of psychoeducation services in addressing various psychological issues among adolescents using the Systematic Literature Review (SLR) method. Following the Kitchenham protocol, the literature selection process was conducted in the Google Scholar and Semantic Scholar databases covering the period from 2016 to 2026. A total of 13 selected articles were analyzed based on the type of psychological issue, target population, mode of implementation, and success rate. The results indicate that psychoeducation is effective in reducing post-traumatic symptoms, addressing alexithymia, managing psychosomatic disorders, and preventing suicidal ideation. The success of the intervention is driven by improvements in participants’ adaptive coping skills and self-awareness. Implementation through school-based programs and digital platforms yielded positive results in improving service accessibility. The study’s conclusions affirm that psychoeducation is an essential preventive and curative strategy for maintaining the psychological well-being of adolescents in the modern era.